Rumeli fortress from the perspective of architecture history - Erismis, Mehmet Cercis; Gezerman, Ahmet Ozan (ELSEVIER, 2013)
The Rumeli Fortress has a unique place in world history. This study presents information on the castle and Fatih period, explains the aspects of castle thought to be important, and discusses the gradually ruined areas of the castle. (C) 2013. Higher Education Press Limited Company. Production and hosting by Elsevier B.V.
Keywords: Architectural research; History research; method; Scientific research; Bogazkesen; Rumeli Fortress; Restoration; HALL; Architecture